Virtual Underground City Osówka - Jabłoński, Mateusz; Lipecki, Tomasz; Jaśkowski, Wojciech; Ochałek, Agnieszka (Geology, Geophysics and Environment, 2016)
Project Riese (German for giant) in Owl Mountains, located in Lower Silesia, is the biggest mining and building project of Nazi Germany. The construction work was done by forced laborers, POWs, and prisoners of concentration camp Gross-Rosen. Many of them lost their lives. Whole project was kept in secret, even the beginning of the construction work is unclear.  The purpose of Riese remains uncertain because of lack of documentation, it is still rather a hypothesis than a fact. The only verified information is that the project was abandoned at the initial stage due to approach of the Red Army. Before that Nazis put a lot of effort to hide all information about Riese. Today we can see how successful these efforts were. Nowdays six underground structures are discovered in Walim and Głuszyca area: Włodarz (3000 meters of tunnels), Osówka (1700 meters of tunnels), Sokolec (or Gontów, 800 meters of tunnels), Soboń (740 meters of tunnels), Rzeczka (560 meters of tunnels), Jugowice (500 meters of tunnels) and about 600 meters of tunnels under Książ Castle in Walbyrzych (Aniszewski 2002, Graba 2012). It has been found that many of the tunnels in some structures have a dead end and there is a theory this might proof that all complexes were supposed to be combined. It is believed that many kilometres of the underground tunnels are still to be discovered (Cera 1998).Whole area is one of the most popular destinations for treasure hunters and scientists. Nowadays treasure hunters are using not only maps and metal detectors, but also GPRs. Scientists are interested in Riese because of many underground tunnels in various sizes and depth, as well as huge amount of steel which was used to reinforce adits. All these details allow scientists to perform many different types of research. Geophysicists are testing the equipment and methodology in the area of gravimetric, magnetic and GPR measurements. All geophysics measurement need to be put into coordinate system, local or global. Moreover in order to eliminate gravity or magnetic effect of the excavations and steel reinforce their shape must be known (Porzucek 2013). To meet the needs of scientists, researchers, tourists and museum authorities, authors of this report, with the help of students, performed full inventory of Complex Osówka. It was performed in 2015 and covered all underground and ground objects.1700 meters of underground tunnels in main part of the complex (Museum of Underground City Osówka) were scanned, together with 130 meters of Sztolnia Wodna (from polish water adit) and two ground objects: Siłownia and Kasyno. These two are suppose to be nuclear energy plant and Hitler’s headquarters or command headquarters (Cera 1998). During measurements laser scanner (Faro, Focus 3D), tachymeter (Topcon, OS103) and GPS receivers (Topcon, HiperPro) for georeferency were used.The collected material was used to analyze geometrical relations between objects of Osówka complex. Report presents location of objects in relations to each other which was not previously verified in research or verified in the other ways. Another inventory result is a virtual museum, available from 1st April for everybody on Museum of Underground City Osówka website (www.osowka.pl). User can virtually explore whole complex, including places where visitors are not allowed. During measurements flooded adits have been also inventoried: the ones in the museum and in Sztolnia Wodna (entrance collapsed in November 2015 and the whole adit is in danger of collapsing). Inventory also included Siłownia (firstly water has been pumped out to allow measurements in the staircase and alleged lift shaft). Another inaccessible place available during virtual tour is shaft connecting the forest near Kasyno to the undergrounds. Virtual tour allows also measuring selected surface or distance between chosen points and checking coordinates or height in particular spot. User can generate a link to a screen which interests him and upload it on any website.It must be said that sharing so many detailed and precise data does not equal allowing to perform any research and measurements in all these spots. Project Riese is located on the land belonging to local government, individuals and National Forests (majority of it). Before taking any actions, area manager must give his permission. It is strictly enforced since the whole „golden train” story in July 2015.Research for the article was funded by statutory research of the Department of Mining Areas Protection, Geoinformatics and Mining Surveying (AGH University of Science and Technology) number 11.11.150.195.